Rubber-like shape memory polymeric materials with repeatable thermal-assisted healing function - Wang, Chang Chun (2013)
A thermo-responsive shape memory polymeric material is reported, which is not only rubber-like from above to below its shape recovery temperature, but also has a repeatable thermal-assisted healing function. The mechanisms behind both features are identified. It is found that while micron-sized inclusions play a part in the shape memory effect (SME), tangled polymer chains contribute to the rubber-like phenomenon and repeatable thermal-assisted healing function atop the SME. This tangling effect enables a perfect combination of high elasticity, SME and repeatable thermal-assisted healing to be simultaneously achieved.